Hard ride to Wichita : a Ralph Compton novel - Compton, Ralph; Galloway, Marcus (Penguin Group, 2013)
Their friendship started with a schoolyard tussle. Now, the need for revenge is what binds Luke Croft and Red Connover together. When Luke taught himself how to fire a Colt, he never imagined he'd turn into a gunman. But when his stepfather's dodgy business dealings turn his life upside down, Luke asks Red to help him destroy the man who murdered his kin. The road to vengeance is long and hard, and the two friends who are barely out of boyhood will need all the help they can get if they want to catch a cold-blooded killer.